Interest Rate Pass-Through : A Meta-Analysis of the Literature - Gregora, Jiri (World Bank, Washington, DC, 2019)
The interest rate pass-through describes how changes in a reference rate (the monetary policy, money market, or T-bill rate) transmit to bank lending rates. This paper reviews the empirical literature on the interest rate pass-through and systematizes it by means of meta-analysis and meta-regressions. The paper finds systematically lower estimated pass-through coefficients in studies that focus on transmission to long-term lending rates, consumer lending rates, and average lending rates. The interest rate pass-through is significantly influenced by country macro-financial and institutional factors. The estimated pass-through tends to be stronger for economies with deeper capital markets (measured by market capitalization). Interestingly, central bank independence rising from lower levels can reduce interest rate pass-through, while central bank independence rising from already high levels can boost the pass-through.